Assessing neuronal mitophagy during development in the nematode Caenorhabditis elegans - Ploumi, Christina; Roussos, Antonis; Palikaras, Konstantinos (Methods in molecular biology (Clifton, N.J.), 2024)
Preserving mitochondrial homeostasis is vital, particularly for the energetically demanding and metabolically active nerve cells. Mitophagy, the selective autophagic removal of mitochondria, stands out as a prominent mechanism for efficient mitochondrial turnover, which is crucial for proper neuronal development and function. Dysfunctional mitochondria and disrupted mitophagy pathways have been linked to a diverse array of neurological disorders. The nematode Caenorhabditis elegans, with its well-defined nervous system, serves as an excellent model to unravel the intricate involvement of mitophagy in developing neurons. This chapter describes the use of Rosella biosensor in C. elegans to monitor neuronal mitophagy, providing a user-friendly platform for screening genes and drugs affecting mitophagic pathways under physiological conditions or in the context of neurodevelopmental pathologies.
Keywords: Caenorhabditis elegans; Development; Mitochondria; mitophagy; Neurodevelopmental diseases; Neurons; Rosella biosensor